MXene / PVDF photo-thermal composite film for seawater evaporation
The photothermal composite film is prepared by blending MXene and PVDF, which solves the problems of energy loss and material corrosion during seawater evaporation, and achieves efficient seawater evaporation and material stability, providing a seawater evaporator for Effective solution.
Patent Information
- Application Number
- CN202411361415.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
AI Technical Summary
The existing photothermal composite films have energy losses, material corrosion and salting out during seawater evaporation, resulting in reduced efficiency and difficulty in floating on the water surface for effective evaporation.
The photothermal composite film was prepared by blending MXene and PVDF. The MXene dispersion was obtained by etching Ti3AlC2 by HCl+LiF, and a film with good hydrophilicity and photothermal conversion performance was prepared by scraping method, and combined with freeze-drying treatment to improve the Stability and efficiency.
It realizes efficient seawater evaporation. The MXene/PVDF composite film has good photothermal conversion performance and hydrophilicity, and can float on the water surface by itself, significantly improving the water evaporation rate and material stability.
Smart Images

Figure CN119241968A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solar interface water vapor conversion, and specifically relates to a MXene / PVDF photothermal composite film for seawater evaporation. Background Art
[0002] As the most common substance on Earth, water is an indispensable guarantee for the survival of every living thing. According to statistics, 70.8% of the Earth's surface area is covered by water, but 97% of it is seawater that cannot be directly used, and less than 3% of the water is fresh water that humans urgently need. Whether it is agricultural irrigation or industrial development, fresh water resources are indispensable. Coupled with the uneven distribution of water resources, about 2 / 3 of the world's population faces varying degrees of fresh water shortage. Therefore, there is an urgent need to find an effective way to solve the shortage of fresh water resources. How to extract fresh water from seawater at low cost and meet the use standards has become one of the key research directions.
[0003] Photothermal composite thin film materials are considered to be a kind of membrane material that absorbs solar energy and can efficiently convert it into thermal energy. It is the core of solar-driven water evaporation technology. However, in the process of photothermal conversion, the low-temperature environment of the surrounding air, water, etc. will cause the photothermal energy to dissipate in it. For example, heat conduction and thermal radiation often occur in the process of photothermal conversion of photothermal composite thin film materials, thereby losing some energy; in addition, due to high temperature and strong light irradiation, some photothermal composite thin film materials may be corroded or degraded, thereby greatly affecting the material performance and shortening the material life. In seawater desalination applications, there is also a salting-out phenomenon. The condensed salt will be adsorbed on the surface of the photothermal composite film, reducing the film's absorption of light and the efficiency of heat conversion, thereby reducing the water evaporation performance of the photothermal composite thin film material. Therefore, the selection of photothermal material components and the structural design of the composite film have become the key. For example, in order to reduce energy loss and improve the photothermal conversion efficiency, an insulating layer is designed on the lower surface of the composite film. At the same time, the surface microstructure of the photothermal composite film material, that is, the surface hydrophilicity and roughness, is regulated. On the one hand, it reduces the transfer of heat to the water body, and on the other hand, it increases the light absorption rate. In addition, by constructing a coating on the membrane surface or regulating the membrane structure, the stability of the photothermal composite film material is significantly improved. Summary of the invention
[0004] In view of this, one of the objects of the present invention is to provide a MXene / PVDF photothermal composite film for seawater evaporation, which has excellent photothermal conversion performance and can float on the water surface while ensuring good hydrophilic properties, providing a basis for the preparation of a seawater evaporator.
[0005] A second object of the present invention is to provide a method for preparing the MXene / PVDF photothermal composite film for seawater evaporation.
[0006] One of the purposes of the present invention is achieved by the following technical solution:
[0007] A MXene / PVDF photothermal composite film, wherein the photothermal composite film is obtained by blending a photothermal conversion material MXene dispersion with PVDF to obtain a casting solution for film coating; the photothermal conversion material MXene is Ti3C2T x A dispersion in water; the photothermal conversion material MXene is obtained by etching Ti3AlC2 with HCl+LiF; the mass ratio of MXene dispersion to PVDF in the MXene / PVDF photothermal composite film is preferably 1:2-4; the mass ratio of MXene net content to PVDF in the MXene / PVDF photothermal composite film is (25-45mg): 3.5g.
[0008] Preferably, the MXene / PVDF photothermal composite film is freeze-dried and then stored.
[0009] Preferably, the step of etching Ti3AlC2 with HCl+LiF is:
[0010] Deionized water and HCl solution were added to a polytetrafluoroethylene container in sequence, and LiF was weighed and added to the hydrochloric acid solution several times. After stirring with a magnetic stirrer until the mixture was uniform, Ti3AlC2 powder was added to the mixture several times and stirred at a constant temperature. After separation and pouring out the supernatant, deionized water was added to the precipitate for ultrasonic cleaning until the pH of the supernatant was 5; ethanol was added to the precipitate, and ultrasonic cleaning and centrifugation were performed in an ice bath environment, and the supernatant was poured out. Deionized water was added to the precipitate, and ultrasonic cleaning and centrifugation were performed to obtain the final product MXene dispersion. The net content of MXene in 1 mL of the dispersion was measured by suction filtration and was 20.5 mg.
[0011] Preferably, the concentration of the HCl solution is 9 mol / L, and the volume ratio of deionized water to the HCl solution in the polytetrafluoroethylene container is 1:3.
[0012] Preferably, the amount of LiF used is 2 g, which is added in multiple times to avoid violent reaction and to mix the materials evenly to achieve a better etching effect.
[0013] Preferably, the constant temperature is 40°C and the stirring time is set to 24-48h.
[0014] Preferably, the constant temperature is 40° C. and the stirring time is set to 48 h.
[0015] Preferably, the supernatant is separated by centrifugation at 3750 r / min for 10 min, and this step is repeated until the pH value of the supernatant is 5.
[0016] Preferably, the ultrasonic cleaning time is set to 1 h in ice bath ultrasound.
[0017] Preferably, the MXene / PVDF photothermal composite film has a thickness of 100-250 μm.
[0018] Preferably, the MXene / PVDF photothermal composite film can float on the water surface. The initial contact angle θ of the MXene / PVDF composite film is less than 90°, showing hydrophilicity. As time goes by, the contact angle continues to decrease, and finally θ=0°, showing complete wetting.
[0019] Preferably, the photothermal composite film promotes the evaporation rate of seawater to be 1.25-1.82 g / (m 2 ·s).
[0020] The second object of the present invention is achieved by adopting the following technical solution:
[0021] The method for preparing the MXene / PVDF photothermal composite film comprises the following steps:
[0022] The MXene dispersion, PVDF, DMAc, and pore-forming agent PVP were added into a beaker in a certain ratio.
[0023] The casting liquid is heated and stirred in an oil bath with a heat-collecting constant temperature heating magnetic stirrer. After the casting liquid is completely mixed, it is placed in a vacuum oven for degassing. The beaker is tilted to pour the casting liquid evenly on the scraping plate. The film thickness is controlled at 100-200μm using a four-sided wet film preparation device. After uniform scraping, the MXene / PVDF membrane and the scraping plate are placed at room temperature for 10-20s, and then quickly placed in water at 25-35℃. After the membrane solvent is exchanged, it falls off from the scraping plate by itself and is freeze-dried for storage.
[0024] Preferably, the mass ratio of the PVDF to the solvent DMAc is 1:5.
[0025] Preferably, the ratio of PVDF, DMAc and pore-forming agent PVP is 6.7:33:1.
[0026] Preferably, the four-sided wet film preparation device of model SZQ purchased from Huaguo Precision Testing Equipment Factory is selected for film scraping, and the film thickness is controlled to be 100 μm.
[0027] Preferably, the stirring temperature is 65° C. when the stirring is heated in an oil bath using a heat-collecting constant-temperature heating magnetic stirrer.
[0028] Preferably, the heating time is 6-24 hours when the oil bath is heated and stirred by a heat-collecting constant temperature heating magnetic stirrer.
[0029] Preferably, the heating time is 6 hours when the oil bath is heated and stirred by a heat-collecting constant temperature heating magnetic stirrer.
[0030] Preferably, the vacuum oven degassing condition is vacuum oven degassing at 35° C. for 1-5 hours.
[0031] Preferably, the freeze-drying temperature is -60°C.
[0032] Preferably, the freeze-drying vacuum degree is 8.5-9.0 Pa, and the drying time is 24-30 h.
[0033] Preferably, the freeze-drying vacuum degree is 8.5 Pa and the drying time is 24 h.
[0034] Compared with the prior art, the beneficial effects of the present invention are mainly:
[0035] The present invention prepares a photothermal composite film by blending MXene and PVDF, and explores the effect of the introduction of MXene on the hydrophilicity and photothermal conversion performance of the MXene / PVDF composite film. MXene has good photothermal conversion performance and hydrophilicity, and PVDF, as a commonly used membrane material, has hydrophobicity. The combination of the two enables the composite film to absorb water while floating on the water surface for interfacial photothermal conversion. The present invention adopts a scraping method to prepare the MXene / PVDF composite film. The overall process is relatively simple, which is convenient for membrane structure characterization and membrane performance testing, and provides a theoretical and practical basis for the construction and application of subsequent seawater evaporators. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0037] Figure 1 This is a schematic diagram of the working principle of the MXene / PVDF composite film of the present invention for seawater evaporation;
[0038] Figure 2 This is a physical picture of the MXene / PVDF composite film prepared in Example 1 of the present invention;
[0039] Figure 3 This is a physical picture of MXene / PVDF composite films with different MXene contents prepared in Example 1 of the present invention;
[0040] Figure 4 This is a graph showing the change in contact angle over time of MXene / PVDF composite films with different MXene contents prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0041] The present invention provides a MXene / PVDF photothermal composite film, comprising preparing a photothermal conversion material MXene, preparing a photothermal composite film, regulating the hydrophilic and hydrophobic properties of the film, and testing the photothermal conversion performance of the film; the photothermal conversion material MXene is Ti3C2T x The dispersion in water; the photothermal conversion material MXene is obtained by etching Ti3AlC2 with HCl+LiF; the film-making photothermal composite film is obtained by blending the MXene dispersion with PVDF to obtain a casting liquid for scraping and film-making; the hydrophilic and hydrophobic properties of the film are regulated by hydrophobic modification of the film and contact angle measurement; the photothermal conversion performance of the film is tested by making the film float on the water surface and using a xenon lamp light source to simulate sunlight for irradiation and measuring the water evaporation rate. The working principle of the MXene / PVDF composite film of the present invention for seawater evaporation is as follows Figure 1 shown.
[0042] In order to further illustrate the present invention, the following is combined with the accompanying drawings and examples, but they should not be understood as limiting the scope of protection of the present invention. Unless otherwise specified, the raw materials used in the present invention are all commercially available.
[0043] Example 1
[0044] This embodiment provides a specific method for preparing a MXene dispersion by etching, comprising the following steps:
[0045] Add 10mL of deionized water and 30mL of 9mol / L HCl solution to a polytetrafluoroethylene container, weigh 2.00g of LiF, add it to the hydrochloric acid solution several times, and stir it with a magnetic stirrer until it is evenly mixed. Add 2.00g of Ti3AlC2 powder to the mixture several times to avoid violent reaction and mix the materials evenly to achieve a better etching effect. This step is completed within ten minutes. The mixture is stirred at a constant temperature of 40℃ for 24h, 36h, and 48h respectively. Centrifuge the product at a speed of 3750r / min for 10min, pour out the supernatant, add deionized water to the precipitate for ultrasonic cleaning for 10min, repeat the cleaning until the supernatant pH=5, add ethanol, and ultrasonically clean it in an ice bath environment for 1h, centrifuge it at 5000r / min for 10min, and then pour out the supernatant. Add 15mL of deionized water to the precipitate, ultrasonically clean it for 20min, centrifuge it at 3750r / min for 10min, and take the supernatant to obtain the final product MXene dispersion.
[0046] The MXene dispersion prepared by etching Ti3AlC2 with HCl+LiF mixed solution at a constant temperature of 40℃ and stirring for 48h had the highest concentration. After filtration, the net content of MXene in 1mL of dispersion was measured to be 20.5mg.
[0047] Example 2
[0048] The PVDF used in this example has a purity of more than 90% and is purchased from Shanghai McLean Biochemical Technology Co., Ltd. It is a white powder with high viscosity and is used for film formation; PVP is purchased from Shanghai McLean Biochemical Technology Co., Ltd. with a specification of AR; DMAc is purchased from Shanghai McLean Biochemical Technology Co., Ltd. with a purity of 99%; Ti3AlC 2、 HCl and LiF were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0049] This embodiment provides a method for preparing a MXene / PVDF photothermal composite film. In order to fully explore the effect of MXene addition and addition amount on the performance of the composite film, 4 different MXene dispersion addition control groups were set up (as shown in Table 1). In the present invention, there is no special requirement for the ratio of the PVDF to the solvent DMAc, and a mass ratio of 1:5 is adopted. The concentration of the MXene dispersion prepared in Example 1 is 20.5 mg / mL, and the mass of MXene in the casting solution is obtained by controlling the volume. The following steps are included:
[0050] Table 1 MXene / PVDF composite film casting liquid ratio
[0051] MXene / mg PVDF / g DMAc / g PVP / g 0 3.5 17.5 0.525 25 3.5 17.5 0.525 35 3.5 17.5 0.525 45 3.5 17.5 0.525
[0052] At room temperature, the MXene dispersion, PVDF, DMAc, and pore-forming agent PVP were put into a beaker according to the proportions in Table 1, and heated and stirred for 6 hours in a heat-collecting constant temperature heating magnetic stirrer oil bath at 65°C to prepare casting solutions with different MXene contents. After the casting solution was completely mixed, it was placed in a vacuum oven at 35°C for degassing for 1 hour. The beaker was tilted, and the casting solution was poured evenly on the scraping plate. The film thickness was controlled at 100-250μm using a four-sided wet film preparation device of model SZQ. After uniform scraping, the MXene / PVDF film and the scraping plate were placed at room temperature for 20s, and then quickly placed in 30°C water, waiting for the membrane solvent to be exchanged and then fall off from the scraping plate. The composite film was placed in a freeze dryer for drying, and the drying conditions were -60°C, vacuum degree 8.5Pa, and drying time 24h to ensure the stability of the composite film performance.
[0053] The thickness of the prepared MXene / PVDF composite film is as follows: Figure 2 The physical appearance of MXene / PVDF composite films with different MXene contents is shown in Figure 3 shown.
[0054] Example 3
[0055] This example tests the hydrophilicity of the MXene / PVDF photothermal composite film provided by the present invention, including the following steps:
[0056] The photothermal composite films with different MXene contents prepared in Example 2 were cut to a size of 2.5 cm × 2.5 cm, and a 30 microliter drop of water was placed on the surface of the MXene / PVDF photothermal composite film using a microsyringe. Ensure that the ambient temperature and humidity are constant to avoid affecting the morphology of the droplets and the measurement results. Use a camera to capture the contact image between the droplet and the surface of the MXene / PVDF photothermal composite film to ensure that the image is clear and the droplet is fully visible. Use a contact angle meter to measure the contact angle between the droplet and the MXene / PVDF photothermal composite film, and record the changes in the contact angle of the MXene / PVDF photothermal composite film with different MXene contents within 0-300s. Perform multiple measurements to obtain an accurate average contact angle value.
[0057] The results are as follows Figure 4 As shown in the figure, the initial contact angle of the pure PVDF film is θ>90°, which is hydrophobic. As time increases, the contact angle decreases but the range of change is not large. After 90s, the contact angle θ=84.80° remains unchanged, and the film as a whole is hydrophobic; the initial contact angle of the MXene / PVDF composite film is θ<90°, which is hydrophilic. As time increases, the contact angle continues to decrease, and finally θ=0°, and the composite film is completely wetted. And as the MXene content increases, the composite film will reach a completely wetted state earlier. This shows that the addition of MXene greatly improves the hydrophilic properties of the film, allowing the film to transport water molecules to the film surface faster during the photothermal conversion process, thereby improving the efficiency of seawater desalination.
[0058] Example 4
[0059] This example tests the water evaporation rate of the MXene / PVDF photothermal composite film provided by the present invention, including the following steps:
[0060] Select the MXene casting liquid with different MXene contents in Table 1 to prepare MXene / PVDF photothermal composite films with different MXene contents of 250μm thickness, cut them into 3cm×3.5cm size, and cover them on the water surface with a volume of 30mL. Set up a water control group without covering the composite film, use a xenon lamp light source to simulate sunlight to irradiate the control group and the experimental group for 40min, observe the temperature change on the film surface, measure the mass of water evaporated under the film coverage, and calculate the water evaporation rate. The water evaporation rate calculation formula is:
[0061]
[0062] Where v is the evaporation rate, Δm is the mass of water evaporated, s is the membrane area, and Δt is the evaporation time.
[0063] The calculation results are shown in Table 4, indicating that the rate at which the MXene / PVDF composite film promotes water evaporation increases with the increase in the MXene content in the composite film. After 40 minutes of illumination, the mass of evaporated water covered by the MXene / PVDF composite film containing 45 mg MXene is 4.59 g, and the water evaporation rate is 1.82 g / (m 2 ·s), which is twice that of pure PVDF film. The speed of water evaporation can reflect the photothermal conversion efficiency of the photothermal composite film.
[0064] Table 1 Water evaporation rate of MXene / PVDF composite films with different MXene contents
[0065] MXene content mg The mass of water evaporated under film coverage g <![CDATA[Water evaporation rate g / (m 2 ·s)]]> 0 2.15 0.85 25 3.15 1.25 35 3.88 1.54 45 4.59 1.82
[0066] From the performance test, it can be seen that the MXene / PVDF photothermal composite film prepared by the present invention has good hydrophilicity and photothermal conversion performance, and can be used for the construction of seawater evaporator.
[0067] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A MXene / PVDF photothermal composite film, characterized in that: The photothermal composite film is prepared by blending a photothermal conversion material MXene dispersion with PVDF to obtain a casting solution, which is then scraped and coated; The photothermal conversion material MXene is Ti3C2T x dispersion in water; The photothermal conversion material MXene is obtained by etching Ti3AlC2 with HCl+LiF; The mass ratio of MXene dispersion to PVDF in the MXene / PVDF photothermal composite film is preferably 1:2-4; The mass ratio of the net content of MXene to PVDF in the MXene / PVDF photothermal composite film is (25-45 mg): 3.5 g.
2. The MXene / PVDF photothermal composite film according to claim 1, characterized in that: The steps of etching Ti3AlC2 with HCl+LiF are as follows: Ti3AlC2 powder was added to the HCl and LiF mixture several times and stirred at a constant temperature for 24h-48h, the supernatant was discarded by centrifugation, and the precipitate was ultrasonically cleaned with deionized water until the pH value was 5; ethanol was added to the precipitate, ultrasonically cleaned in an ice bath environment, centrifuged and discarded the supernatant, deionized water was added to the precipitate for ultrasonic cleaning, and the supernatant was centrifuged to obtain the final product MXene dispersion.
3. The MXene / PVDF photothermal composite film according to claim 1, characterized in that: The photothermal composite film has a thickness of 100-250 μm.
4. The MXene / PVDF photothermal composite film according to claim 1, characterized in that: The MXene / PVDF photothermal composite film can float on the water surface. The initial contact angle θ of the MXene / PVDF composite film is less than 90°, which shows hydrophilicity. As time goes by, the contact angle continues to decrease, and finally θ=0°, which shows complete wetting.
5. The MXene / PVDF photothermal composite film according to claim 1, characterized in that: The photothermal composite film promotes the evaporation rate of seawater to 1.25-1.82 g / (m 2 ·s).
6. The method for preparing the MXene / PVDF photothermal composite film according to any one of claims 1 to 4, comprising the following steps: The MXene dispersion, PVDF, DMAc and pore-forming agent PVP are added to a beaker in a certain ratio, heated and stirred in an oil bath, and after the casting liquid is completely mixed, it is placed in a vacuum oven for degassing; the casting liquid is poured evenly on a scraping plate, and after scraping at a uniform speed, the MXene / PVDF membrane and the scraping plate are placed at room temperature for 10-20 seconds, and then quickly placed in water at 25-35°C, waiting for the membrane solvent to be exchanged and then fall off from the scraping plate by itself, and stored after freeze-drying.
7. The method for preparing the MXene / PVDF photothermal composite film according to claim 6, characterized in that: The mass ratio of the PVDF to the solvent DMAc is 1:
5.
8. The method for preparing the MXene / PVDF photothermal composite film according to claim 5, characterized in that: The ratio of PVDF, DMAc and pore-forming agent PVP is 6.7:33:
1.
9. The method for preparing the MXene / PVDF photothermal composite film according to claim 5, characterized in that: The oil bath heating and stirring time is 6-24 hours, and the vacuum oven is used for degassing at 35° C. for 1-5 hours.
10. The method for preparing the MXene / PVDF photothermal composite film according to claim 5, characterized in that: The freeze-drying temperature is -60°C, the vacuum degree is 8.5-9.0Pa, and the drying time is 24-30h.
Citation Information
Cited By
Water evaporation power generation device based on MXene / filter paper composite film and preparation method thereof
CN120474381A
A water evaporation power generation device based on MXene / filter paper composite film and its preparation method
CN120474381B
Integrated passive water taking device and system based on MXene interface evaporation and radiation refrigeration
CN121063625A
